A Long Way to Go for Diversity: The Fight Portrayed by Inter-faith Harmony Forum in Malang Raya - Hipolitus Kristoforus Kewuel (Jurnal Moral Kemasyarakatan, 2020)
Religious diversity has been one of the important aspects that require explicit regulation on UUD 1945. The implementation of this law is done continuously as a part of state responsibility in ensuring the religious life of its people. The Inter-faith Harmony Forum (FKUB) is regulated under the Joint Decree of the Minister of Religion and Minister of Home Affairs No. 9 and No. 8 of 2006 as a revision of the Two Ministerial Decree No. 1, 1969. FKUB becomes an official forum in the central, province, and district/city levels. This research aimed at revealing to what extent the honorable forum effectively carries out its mission. Qualitative ethnographic was employed from data collection to data processing method. The research results show that FKUB's effort to instill the value of religious diversity is not only challenged by the pluralistic society, but also by the government as the initiator of this forum.